FACTORS INFLUENCING FOOD FORTIFICATION AS A MEANS TO COMBAT MALNUTRITION AMONG CHILDREN ATTENDING IMMUNIZATION AT NAKASONGOLA HEALTH CENTER IV. A CROSS-SECTIONAL STUDY. - Bukenya , Arthur Matthew; Negesa, Justine (Student’s Journal of Health Research Africa, 2023)
Introduction: Objectives: To determine the factors influencing food fortification as a means to combat malnutrition among children attending immunization whereas the specific objectives were to assess the knowledge of caretakers, ascertain the attitude, and determine the practices affecting food fortification as a means to combat malnutrition among children attending immunization at Nakasongola Health center IV. Methods: A cross-sectional study was conducted in the district at Nakasongola Health Center IV. Simple random sampling was used to recruit 100 respondents who had brought children for immunization and data was analyzed using Excel. Results: The results from this study revealed that more than 50% of the participants were not aware of the term ‘food fortification’. Most of the participants (86%) were not aware of the fact that the Ugandan government made food fortification compulsory on staple foods and the majority of the respondents reported their source of information as health personnel 63(63.0%). Over 60% of the caretakers reported that they cooked fortified foods in the same way as unfortified foods while 33% cooked the fortified food differently. Most participants (90%) of the respondents think food fortification is important, 22% of the respondents read food labels before buying food while only 2% of the respondents feed their children on fortified food. Conclusion: Overall, the study suggests that while there is some level of awareness and positive attitude towards food fortification among caretakers of children attending immunization at Nakasongola Health Center IV, there is still a need for further education and promotion of food fortification practices. This can be achieved through increased awareness campaigns and education by health workers and other stakeholders. Recommendation: Education and awareness campaigns should be conducted to increase knowledge about food fortification, its benefits, and the use of fortified foods among the population.